The Impact of M&A Delistings on the Information Environment of Industry Peer Firms - Brown, Anna Bergman; Byard, Donal; Darrough, Masako; Suh, Jangwon (The Accounting Review, 2024)
ABSTRACT This study documents that M&A delistings are associated with a deterioration in the quality of analysts’ information environment for industry peer firms, measured by an increase in analysts’ absolute forecast errors and dispersion. This effect persists for six quarters and is larger when the delisting target firm contributes relatively more to the industry information environment. Further, we find that, among analysts forecasting earnings for an industry peer firm, those who also followed the delisted target firm in the pre-M&A period experience a larger increase in their absolute forecast errors. A comparison based on public versus private target firms also suggests that the loss of target firms’ public disclosures plays a role in the deterioration in the quality of analysts’ information environment. In additional analyses, we find evidence consistent with this effect resulting from a deterioration in analysts’ ability to exploit across-firm information complementarities. JEL Classifications: G14; G18; G34; M40.